Exact maps of the pseudo-arc - Mouron, Chris (Topology Proceedings, 2022)
In this paper, we provide a method of constructing a topologically exact map of the pseudo-arc using diagonal factor maps on the inverse limit space. Additionally, we give some criteria that guarantee when a topologically exact map of the pseudo-arc has infinite entropy.